Earthquakes - Ohare, Ted; Nang Chan Yeema (Los Angeles, California, United States Fitzgerald Books, 2007)
Illustrations and text introduce earthquakes from their history and causes, to how they are measured and where they occur.
Keywords: Juvenile Nonfiction